Social construction of the community for the development of the alley of Huaylas, Caraz - Paredes Tarazona, Mildred (2004)
OBJECTIVE: Describe the psycho social dimensions of the organizational construction of the Andean communities Cruz De Mayo, Pamapacocha, Queral, Miramar and Cajabamba. Determine the elements of identity and diversity that create the perception that the people have about their community. MATERIAL AND METHOD: Ninety Seven individuals were interviewed sixteen years of age or older with the translated Creo C questionnaire. A discriminate analysis was used to evaluate the translated forms of the Creo C questionnaire. The Chi Cuadrado De Pearson was used to evaluate the results from the questionnaire after interviewing was complete. RESULTS: Using a scale from one to four, in perception, productivity was the more important element that scaled 3.15 opposed to retribution at 2.14. When interviewed about their satisfaction, identity was higher at 3.17 opposed to hazard at 1.85. The standardized coefficients from the discriminative function indicate that each community is particular and helps distinguish individuals from one community to another by 97% to 100%, enough for certainty. CONCLUSIONS: Each community shares and develops the representation of the community that is particular. The Creo C is valid to use and analyze the group representation that the individuals have from their communities. The sense of belonging to a small village is the most powerful variable for group representation and to distinguish the perception that the members have about their community. Identity to small villages determine the subjective exchange. The low number of variables that distinguish the community suggests that identity exist in the community.